2020
DOI: 10.20944/preprints202006.0240.v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

COVID-19 Contact Tracing: Challenges and Future Directions

Abstract: Contact tracing has become a vital tool for public health officials to effectively combat the spread of new diseases, such asthe novel coronavirus disease COVID-19. Contact tracing is not new to epidemiologist rather, it used manual or semi-manualapproaches that are incredibly time-consuming, costly and inefficient. It mostly relies on human memory while scalabilityis a significant challenge in tackling pandemics. The unprecedented health and socio-economic impacts led researchersand practitioners around the w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…The PEPP-PT app was initially touted by its creators as having a 90% true-positive and 10% false-negative rate [ 51 ]. However, several studies since have indicated that Bluetooth-based proximity tracing may have significantly high error rates.…”
Section: Key Considerations In App Design and Categoriesmentioning
confidence: 99%
“…The PEPP-PT app was initially touted by its creators as having a 90% true-positive and 10% false-negative rate [ 51 ]. However, several studies since have indicated that Bluetooth-based proximity tracing may have significantly high error rates.…”
Section: Key Considerations In App Design and Categoriesmentioning
confidence: 99%
“…However, there remain important challenges to scaling contact tracing (Chowdhury et al 2020;Quilty et al 2021;Kretzschmar et al 2020) that could hinder its eectiveness during signicant outbreaks.…”
Section: Resultsmentioning
confidence: 99%
“…As the proximity of users is being broadcasted at all times with these apps along with their personal data, users can become suspicious about being surveilled by their government. Therefore, the information being shared by users must be handled lawfully, with user consent, and in compliance with the GDPR to keep personal information private and identities anonymous [48,49]. Some countries like China and India have made their contact tracing app mandatory for every citizen, while others have made it voluntary whereby only interested users can download and use it.…”
Section: Discussionmentioning
confidence: 99%